2014
DOI: 10.1089/thy.2013.0246
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G Is Differentially Expressed in Thyroid Tissues

Abstract: The gradual increase of HLA-G expression from hyperplasia to carcinomas, and the association of strong HLA staining with some variables implicated in poor prognosis corroborate the unfavorable role of HLA-G in tumor thyroid cells, inhibiting cytotoxic immune system cells and facilitating tumor evasion and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 38 publications
0
37
1
Order By: Relevance
“…However, thyroid cancer is found in 5%-10% of the cases, and it is the most common malignant neoplasia of the endocrine system. PTC and FTC are classified as differentiated tumors, represent 90% of the cases, and are derived from follicular cells (3). Early diagnosis and treatment of thyroid cancer is crucial for improved prognosis and a better survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, thyroid cancer is found in 5%-10% of the cases, and it is the most common malignant neoplasia of the endocrine system. PTC and FTC are classified as differentiated tumors, represent 90% of the cases, and are derived from follicular cells (3). Early diagnosis and treatment of thyroid cancer is crucial for improved prognosis and a better survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…We studied 135 patients with malignant and benign thyroid diseases who underwent thyroidectomy from 2000 to 2011 and were followed up at the Thyroid Outpatient Clinic of the Division of Endocrinology of FMRP‐USP. We selected these patients from our previous study of HLA‐G expression in thyroid tissues . DNA was extracted from peripheral blood mononuclear cells obtained from 72 papillary thyroid carcinomas (PTC), 22 follicular thyroid carcinomas (FTC), 19 follicular adenomas (FA) and 21 colloid goitres.…”
Section: Methodsmentioning
confidence: 99%
“…Goitre hyperplastic areas exhibit weak expression, benign lesions present mild expression, and in malignant thyroid neoplasia HLA‐G is strongly expressed. In addition, risk factors associated with worse prognosis, including tumour size and the presence of papillary classic histological subtype in thyroid carcinoma (PTC), were associated with increased HLA‐G expression . Other authors have also observed increased HLA‐G expression in specimens of patients exhibiting PTC and increased plasma soluble HLA‐G (sHLA‐G) levels in patients .…”
Section: Introductionmentioning
confidence: 99%
“…However, more studies on the complete HLA-G gene and its linkage disequilibrium with other genes and on HLA-G expression at both the tumor site and plasma in a specific microenvironment are required to consolidate these findings. carcinoma (69,70), esophageal squamous cell carcinoma (71)(72)(73)(74), gastric cancer (75)(76)(77), glioblastoma (78), hepatocellular carcinoma (79)(80)(81), lung cancer (82)(83)(84), nasopharyngeal carcinoma (85), oral cavity squamous cell carcinoma (86), ovarian cancer (87-89), pancreatic adenocarcinoma (90), thyroid carcinoma (91,92). These data were summarized in Table 1.…”
Section: Relevance Of Hla-g Expression In Cancersmentioning
confidence: 99%